Copper Catalyzed C(sp3)–H Bond Alkylation via Photoinduced Ligand-to-Metal Charge Transfer - Treacy, Sean M; Rovis, Tomislav (Journal of the American Chemical Society, 2021)
Utilizing catalytic CuCl2 we report the functionalization of numerous feedstock chemicals via the coupling of unactivated C(sp3)–H bonds with electron-deficient olefins. The active cuprate catalyst undergoes Ligand-to-Metal Charge Transfer (LMCT) to enable the generation of a chlorine radical which acts as a powerful hydrogen atom transfer reagent capable of abstracting strong electron-rich C(sp3)–H bonds. Of note is that the chlorocuprate catalyst is an exceedingly mild oxidant (0.5 V vs SCE) and that a proposed protodemetalation mechanism offers a broad scope of electron-deficient olefins, offering high diastereoselectivity in the case of endocyclic alkenes. The coupling of chlorine radical generation with Cu reduction through LMCT enables the generation of a highly active HAT reagent in an operationally simple and atom economical protocol.